Sixth Order Differential Equation

Calculus Level 5

f f satisfies

f ( x ) = 1 10 x 3 ( 1 10 x 3 f ( 6 ) ( x ) + 9 10 x 2 f ( 5 ) ( x ) + 9 5 x f ( 4 ) ( x ) + 3 5 f ( 3 ) ( x ) ) , f(x)=-\frac{1}{10} x^3 \left(\frac{1}{10} x^3 f^{(6)}(x)+\frac{9}{10} x^2 f^{(5)}(x)+\frac{9}{5} x f^{(4)}(x)+\frac{3}{5} f^{(3)}(x)\right),

f ( 1 ) = 0 f(1)=0 , f ( 1 ) = 0 f'(1)=0 , f ( 1 ) = 0 f''(1)=0 , f ( 3 ) ( 1 ) = 0 f^{(3)}(1)=0 , f ( 4 ) ( 1 ) = 0 f^{(4)}(1)=0 , and f ( 5 ) ( 1 ) = 520 3 f^{(5)}(1)=\dfrac{520}{3}

If f ( e π ) = e a π e π f(e^{\pi})=e^{a \pi }-e^{-\pi } , where a a is an integer, find a a .


The answer is 3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Mark Hennings
Nov 26, 2017

Looking for solutions of the form x u x^u , we see that we must satisfy the equation u ( u 1 ) ( u 2 ) ( u 3 ) ( u 4 ) ( u 5 ) + 9 u ( u 1 ) ( u 2 ) ( u 3 ) ( u 4 ) + 18 u ( u 1 ) ( u 2 ) ( u 3 ) + 6 u ( u 1 ) ( u 2 ) = 100 u 2 ( u 1 ) 2 ( u 2 ) 2 + 100 = 0 \begin{aligned} u(u-1)(u-2)(u-3)(u-4)(u-5) + 9u(u-1)(u-2)(u-3)(u-4) + 18u(u-1)(u-2)(u-3) + 6u(u-1)(u-2) & = \; -100 \\ u^2(u-1)^2(u-2)^2 + 100 & = \; 0 \end{aligned} which has solutions u = 1 ± i , u = 1 ± 2 i , 3 ± i u = -1\pm i\,,\, u = 1\pm2i\,,\, 3 \pm i . Thus the general solution of the differential equation is f ( x ) = A cos ( ln x ) + B sin ( ln x ) x + x ( C cos ( 2 ln x ) + D sin ( 2 ln x ) ) + x 3 ( E cos ( ln x ) + F sin ( ln x ) ) x > 0 f(x) \; = \; \frac{A \cos(\ln x) + B\sin(\ln x)}{x} + x\big(C\cos(2\ln x) + D\sin(2\ln x)\big) + x^3\big(E\cos(\ln x) + F\sin(\ln x)\big) \hspace{2cm} x > 0 for constants A , B , C , D , E , F A,B,C,D,E,F . Matching the initial conditions, we deduce that f ( x ) = 3 cos ( ln x ) + 2 sin ( ln x ) 3 x + 4 3 x sin ( 2 ln x ) 1 3 x 3 ( 3 cos ( ln x ) 2 sin ( ln x ) ) x > 0 f(x) \; = \; \frac{3\cos(\ln x) + 2\sin(\ln x)}{3x} + \tfrac43x\sin(2\ln x) - \tfrac13x^3\big(3\cos(\ln x) - 2\sin(\ln x)\big) \hspace{2cm} x > 0 and this gives f ( e π ) = e 3 π e π f(e^\pi) = e^{3\pi} - e^{-\pi} , making the answer 3 \boxed{3} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...